2020
DOI: 10.1038/s41467-020-15104-3
|View full text |Cite
|
Sign up to set email alerts
|

Cancer associated fibroblast FAK regulates malignant cell metabolism

Abstract: Emerging evidence suggests that cancer cell metabolism can be regulated by cancerassociated fibroblasts (CAFs), but the mechanisms are poorly defined. Here we show that CAFs regulate malignant cell metabolism through pathways under the control of FAK. In breast and pancreatic cancer patients we find that low FAK expression, specifically in the stromal compartment, predicts reduced overall survival. In mice, depletion of FAK in a subpopulation of CAFs regulates paracrine signals that increase malignant cell gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(81 citation statements)
references
References 74 publications
2
77
0
Order By: Relevance
“…A recent publication identified, using molecular and functional analyses of several patient‐derived CAF primary cultures, four CAF sub‐groups that co‐exist within a tumour, each featuring specific phenotype and prognostic value (Neuzillet et al , 2019). While we were preparing this manuscript, the Hodivala‐Dilke's group showed that FAK depletion in a subpopulation of CAFs (FSP1‐positive) metabolically increases pancreatic tumour growth in mice and that low FAK gene expression within CAFs is associated with poor PDAC patient survival (Demircioglu et al , 2020). FAK role depends on both its scaffolding and kinase activities, and our FAK ‐inactivating strategy mimics the pharmacological inhibition as FAK‐KD mutant retains the cytoplasmic and nuclear scaffolding functions of FAK, which is not the case when FAK gene is invalidated (Demircioglu et al , 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent publication identified, using molecular and functional analyses of several patient‐derived CAF primary cultures, four CAF sub‐groups that co‐exist within a tumour, each featuring specific phenotype and prognostic value (Neuzillet et al , 2019). While we were preparing this manuscript, the Hodivala‐Dilke's group showed that FAK depletion in a subpopulation of CAFs (FSP1‐positive) metabolically increases pancreatic tumour growth in mice and that low FAK gene expression within CAFs is associated with poor PDAC patient survival (Demircioglu et al , 2020). FAK role depends on both its scaffolding and kinase activities, and our FAK ‐inactivating strategy mimics the pharmacological inhibition as FAK‐KD mutant retains the cytoplasmic and nuclear scaffolding functions of FAK, which is not the case when FAK gene is invalidated (Demircioglu et al , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…While we were preparing this manuscript, the Hodivala‐Dilke's group showed that FAK depletion in a subpopulation of CAFs (FSP1‐positive) metabolically increases pancreatic tumour growth in mice and that low FAK gene expression within CAFs is associated with poor PDAC patient survival (Demircioglu et al , 2020). FAK role depends on both its scaffolding and kinase activities, and our FAK ‐inactivating strategy mimics the pharmacological inhibition as FAK‐KD mutant retains the cytoplasmic and nuclear scaffolding functions of FAK, which is not the case when FAK gene is invalidated (Demircioglu et al , 2020). Another explanation for differences between ours and published results (Demircioglu et al , 2020) is that FAK expression and/or signalling may be heterogeneous across patient tumours and within different CAF subsets in a same tumour, putatively explaining different biological consequences for FAK targeting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some CAFs subpopulations have also been shown to reorganize cancer cell metabolism via secreting cytokines that favor glycolysis and TCA cycle intermediates production, resulting in tumor growth and invasion in breast and pancreatic cancers [ 21 ]. A similar cytokine-based interaction was shown in ovarian cancer, implying IL-6, CXCL-5 and CXCL-10, which promotes self-stored glycogen utilization by cancer cells to fuel glycolysis and subsequent mitochondrial activity [ 22 ].…”
Section: Cafs Sustain Cancer Cells Mitochondriamentioning
confidence: 99%
“…CAFs also modulate glycolytic metabolism in cancer cells. Downregulation of focal adhesion kinase in CAFs increases CCL6 and CCL12 expression, leading to elevated glycolysis in cancer cells [ 47 ]. CAFs educated by neighboring cancer cells reversely secrete cytokines to stimulate glycogen metabolism in cancer cells, which accelerates energy production and tumor progression [ 48 ].…”
Section: Cancer-associated Fibroblasts (Cafs)mentioning
confidence: 99%